Preparation of a Hollow Fiber Membrane Made of Antifouling PVDF/Zeolite using the Dip-Coating Technique - Adinda Yufriza; Husna Wardati; Zuhriah Mumtazah; Reva Edra Nugraha; Ditta Kharisma Yolanda Putri; Meta Fitri Rizkiana (University of Jember, 2023)
The practical technique for membrane modification is dip coating. This study coats a PVDF hollow fiber membrane-based composite with a zeolite coating. The composite is made of a polyvinylidene fluoride (PVDF) membrane. The separation capabilities and propensities of composite membranes for organic impurities were examined during water filtering. Fourier-transform infrared spectroscopy analysis of the findings demonstrated that the Zeolite coating was successfully deposited on the PVDF membrane. The flux recovery ratio increases from 69% to 80% while the relative flux drop decreases from 63% to 50%. A composite PVDF membrane dip-coating of Zeolite with a GA and H2SO4 ratio of 1:2 is needed to remove about 75% of humic compounds from effluent. This study's results show that adding Zeolite with a GA and H2SO4 layer can significantly improve the PVDF hollow fiber membrane's hydrophilicity, selectivity, and anti-organic fouling.